2018
DOI: 10.3847/1538-4357/aad7fe
|View full text |Cite
|
Sign up to set email alerts
|

An Analytical Portrait of Binary Mergers in Hierarchical Triple Systems

Abstract: With better statistics and precision, eccentricity could prove to be a useful tool for understanding the origin and environment of binary black holes. Hierarchical triples in particular, which might be abundant in globular clusters and galactic nuclei, could generate observably large eccentricity at LIGO and future gravitational wave detectors. Measuring the eccentricity distribution accurately could help us probe the background and the formation of the mergers. In this paper we continue our previous investiga… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(56 citation statements)
references
References 87 publications
0
56
0
Order By: Relevance
“…A similar result for T m , but neglecting singly-averaged effects 5 (i.e. with e max = e max ), has been previously used by several authors to calculate merger times of binaries driven to high eccentricity via the LK mechanism (Thompson 2011;Antonini & Perets 2012;Liu & Lai 2018;Grishin et al 2018;Randall & Xianyu 2018).…”
Section: Merger Time T Mmentioning
confidence: 73%
“…A similar result for T m , but neglecting singly-averaged effects 5 (i.e. with e max = e max ), has been previously used by several authors to calculate merger times of binaries driven to high eccentricity via the LK mechanism (Thompson 2011;Antonini & Perets 2012;Liu & Lai 2018;Grishin et al 2018;Randall & Xianyu 2018).…”
Section: Merger Time T Mmentioning
confidence: 73%
“…This type of evolution is analogous to the 'fast' type of mergers occurring in black hole triple systems (e.g., Randall & Xianyu 2018), or stellar/planetary systems in which tidal friction is important (e.g., Petrovich 2015).…”
Section: Nonzero Ejection/accretion Radiimentioning
confidence: 92%
“…It has been shown that aLIGO can distinguish eccentric stellar-mass compact binary mergers from circular ones for e  0.05-0.081 at 10 Hz (Lower et al 2018;Gondán & Kocsis 2019). Broadly speaking, mergers from dynamical channels are expected to be more eccentric in the LIGO band than mergers from isolated binary evolution in the field, which are expected to be predominantly circular (e.g., O' Leary et al 2009;Cholis et al 2016;Gondán et al 2018b;Lower et al 2018;Rodriguez et al 2018b;Randall & Xianyu 2018;Samsing 2018;Zevin et al 2019). Among dynamical merger channels, some channels are predicted to yield more eccentric mergers than others.…”
Section: Discussionmentioning
confidence: 99%